Étude exploratoire des obstacles à la transition universitaire selon le vécu d’étudiants français et belges - Mikaël De Clercq; Cathy Perret (Éducation et Socialisation)
Transition to Higher Education constitutes a challenging adjustment step for students that deserves major investigation. Yet, the transition obstacles are still overlooked. Most of international studies focused on individual predictors of adjustment and consider transition to Higher Education as a universal and invariant process. However, contextual characteristics of educational environment should be considered because they don’t imply the same requirements for adjustment. In order to address this limitation, this paper realized an exploratory comparison of first year student experience between a French and a Belgian university. The results highlighted similarities and important changes in student’s experience. For example, girls from underprivileged background tend to express more difficulties in Belgium and more important program differences were observed in France. The discussion and future perspective propose new rationales to address context diversity in Higher Education.